Frequency and Biodiversity of 2,4-Diacetylphloroglucinol-Producing Bacteria Isolated from the Maize Rhizosphere at Different Stages of Plant Growth - Picard, C. (American Society for Microbiology, 2000)
A Pseudomonas 2,4-diacetylphloroglucinol (DAPG)-producing population that occurred naturally on the roots, in rhizosphere soil of Zea mays and in the nonrhizosphere soil was investigated in order to assess the microbial diversity at five stages of plant growth. A total of 1,716 isolates were obtained, and 188 of these isolates were able to produce DAPG. DAPG producers were isolated at each stage of plant growth, indicating that the maize rhizosphere is colonized by natural DAPG producers throughout development. The frequency of DAPG producers was very low in the first stage of plant growth and increased over time. An analysis of the level of biodiversity of the DAPG producers at the species level was performed by comparing the AluI restriction patterns of the 16S ribosomal DNAs (rDNAs) amplified by PCR from 167 isolates. This comparison allowed us to cluster the isolates into four amplified rDNA restriction analysis (ARDRA) groups, and the main group (ARDRA group 1) contained 89.8% of the isolates. The diversity of the 150 isolates belonging to ARDRA group 1 was analyzed by the random amplified polymorphic DNA (RAPD) technique. An analysis of RAPD patterns by a molecular variance method revealed that there was a high level of genetic diversity in this population and that the genetic diversity was related to plant age. Finally, we found that some of the DAPG producers, which originated from all stages of plant growth, had the same genotype. These DAPG producers could be exploited in future screening programs for biocontrol agents.